Elevation and land use shape soil entomopathogenic fungal communities in the Uluguru mountains, Tanzania: Insights from metagenomic and culture-based approaches - Abel Jonathan Mussa; Joseph O. Ruboha; Sija A. Kabota; Martin J. Martin; Maulid W. Mwatawala (PLoS ONE, 2026)
Background Soil-borne entomopathogenic fungi (EPFs) support ecological regulation of pests, yet their distribution across tropical mountain agroecosystems is poorly characterized. The study conducted between April and December 2024, evaluated diversity and distribution of soil EPF along the Uluguru Mountains slopes in Morogoro, Tanzania. Methods Twenty-four soil samples were collected from cultivated and fallow soils at low (518 m), medium (1100 m), and high (1700 m) elevations on the Uluguru slopes (Morogoro, Tanzania). Amplicon sequencing of the ITS region profiled fungal communities, and selective isolation with ITS barcoding confirmed cultivable taxa. Diversity indices, Bray-Curtis dissimilarity, Principal Coordinate Analysis (PCoA), and PERMANOVA evaluated patterns across elevation and land use. Results Fourteen EPF species in 12 genera were detected, dominated by Ophiocordycipitaceae (56.1%) and Clavicipitaceae (37.8%). Purpureocillium lilacinum, Metarhizium anisopliae, Clonostachys rosea, and Pochonia chlamydosporia were widespread. Cultivated soils at medium- and high elevations showed greater richness and diversity (1.37 and 1.57) than fallows (0.64 and 0.48) respectively, while high-altitude fallows were strongly dominated by Metapochonia suchlasporia . Community composition clustered by land use, with elevation as a secondary driver (PERMANOVA p = 0.06). Selected P. lilacinum and C. rosea species caused 10–50% mortality of Spodoptera frugiperda larvae in preliminary laboratory assays. Conclusions Elevation and land use jointly structure EPF communities in the Uluguru Mountains. Some taxa showed preliminary pathogenicity in laboratory assays, indicating potential for future evaluation as biological control agents in smallholder farming systems. Public deposition of sequencing reads will facilitate reuse and benchmarking.